Group Divisible Designs with Two Associate Classes and 𝜆2=1 - Nittiya Pabhapote; Narong Punnim (International Journal of Mathematics and Mathematical Sciences)
The original classiffcation of PBIBDs defined group divisible designs GDD(𝑣=𝑣1+𝑣2+⋯+𝑣𝑔,𝑔,𝑘,𝜆1,𝜆2) with 𝜆1≠0. In this paper, we prove that the necessary conditions are suffcient for the existence of the group divisible designs with two groups of unequal sizes and block size three with 𝜆2=1.